Preparation of a novel carbonaceous material for Cr(VI) removal in aqueous solution using oily sludge of tank bottom as a raw material. Issue 1 (February 2019) - Yang, Huifen; Shen, Kang; Fu, Peng; Zhang, Ge
Abstract: A novel carbonaceous material (NCM) for Cr(VI) removal from aqueous solution was prepared by pyrolysis using the oily sludge of tank bottom as a raw material. The NCM obtained was characterized by chemical analysis, XRD, SEM-EDS, FTIR and ASAP2010 specific surface porosity tester. The results showed that the NCM exhibited a strong Cr(VI) removal capacity because of the presence of low-valent sulfur compounds in NCM. The maximun removal rate of Cr(VI) was 93.5% when the solution containing 40 mg/L Cr(VI) was treated using 1.0 g/L NCM, prepared under the optimum conditions at a pyrolysis temperature of 750 ℃, a heating rate of 4 ℃/min, a nitrogen gas flow of 150 ml/min and a pyrolysis time of 60 min. NCM was an inorganic material containing 22.70% carbon. Elements C, S, Fe, Al, Ca and Si constituted the porous skeleton structure of NCM. The element C in the material partly existed in group −CH3, −CH2 - and C–S. The elements S, Fe, Al, Ca and Si were partly embedded in NCM in the forms of crystalline minerals such as CaAl2 Si2 O8, CaS, FeS, Fe1-x S and Fe7 S8 . The pore size distribution was mainly in the range of 35 to 500 nm inside NCM. It has been proven for the first time that an oily sludge of tank bottom can be used to prepare the NCM for Cr(VI) removal by using a pyrolytic technique.